Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Fill in the missing steps for the derivation of the quadratic formula using the choices below:

[tex]\[
\begin{array}{l}
c+\frac{b}{2a} = \frac{\pm \sqrt{b^2-4ac}}{2a} \\
x^2 + \frac{b}{a}x = \frac{-c}{a} \\
x = \frac{-b \pm \sqrt{b^2-4ac}}{2a} \\
\left(x + \frac{b}{2a}\right)^2 = \frac{-4ac + b^2}{4a^2}
\end{array}
\][/tex]

Step 1: [tex]\(ax^2 + bx + c = 0\)[/tex]

Step 2: [tex]\(ax^2 + bx = -c\)[/tex]

Step 3: [tex]\(\square\)[/tex]

Step 4: [tex]\(x^2 + \frac{b}{a}x + \frac{b^2}{4a^2} = \frac{-c}{a} + \frac{b^2}{4a^2}\)[/tex]

Step 5: [tex]\(\square\)[/tex]

Step 6: [tex]\(\square\)[/tex]

Step 7: [tex]\(x = -\frac{b}{2a} \pm \frac{\sqrt{b^2-4ac}}{2a}\)[/tex]

Step 8: [tex]\(\square\)[/tex]


Sagot :

To find the missing steps of the derivation for the quadratic formula, we'll follow these steps:

1. Given Equation:
[tex]\[ a x^2 + b x + c = 0 \][/tex]

2. Isolate [tex]\( c \)[/tex]:
[tex]\[ a x^2 + b x = -c \][/tex]

3. Convert to simpler quadratic form by dividing through by [tex]\( a \)[/tex]:
[tex]\[ x^2 + \frac{b}{a} x = -\frac{c}{a} \][/tex]

4. Complete the square on the left side:
[tex]\[ x^2 + \frac{b}{a} x + \left(\frac{b}{2a}\right)^2 = -\frac{c}{a} + \left(\frac{b}{2a}\right)^2 \][/tex]

5. Simplify and write the left side as a perfect square:
[tex]\[ \left(x + \frac{b}{2a}\right)^2 = \frac{b^2 - 4ac}{4a^2} \][/tex]

6. Take the square root of both sides:
[tex]\[ x + \frac{b}{2a} = \pm \frac{\sqrt{b^2 - 4ac}}{2a} \][/tex]

7. Solve for [tex]\( x \)[/tex] by isolating it:
[tex]\[ x = -\frac{b}{2a} \pm \frac{\sqrt{b^2 - 4ac}}{2a} \][/tex]

So the missing steps are:

- Step 3:
[tex]\[ x^2 + \frac{b}{a} x = -\frac{c}{a} \][/tex]

- Step 5:
[tex]\[ \left(x + \frac{b}{2a}\right)^2 = \frac{b^2 - 4ac}{4a^2} \][/tex]

- Step 8:
[tex]\[ x = -\frac{b}{2a} \pm \frac{\sqrt{b^2 - 4ac}}{2a} \][/tex]

So, the steps now look like this:
1. [tex]\( a x^2 + b x + c = 0 \)[/tex]
2. [tex]\( a x^2 + b x = -c \)[/tex]
3. [tex]\( x^2 + \frac{b}{a} x = -\frac{c}{a} \)[/tex]
4. [tex]\( x^2 + \frac{b}{a} x + \frac{b^2}{4a^2} = -\frac{c}{a} + \frac{b^2}{4a^2} \)[/tex]
5. [tex]\(\left(x + \frac{b}{2a}\right)^2 = \frac{b^2 - 4ac}{4a^2} \)[/tex]
6. [tex]\( x + \frac{b}{2a} = \pm \frac{\sqrt{b^2 - 4ac}}{2a} \)[/tex]
7. [tex]\( x = -\frac{b}{2a} \pm \frac{\sqrt{b^2 - 4ac}}{2a} \)[/tex]

These missing steps complete the derivation of the quadratic formula.